Maqom - A Classic of The Peoples of The East The Source of Music Traditions (Journal of Pedagogical Inventions and Practices, 2022)
This article discusses the classical music of the peoples of the East, as well as their importance and role in social life, as well as the direction and style of performance of traditional classical music.